Coupling of Magnetic and Elastic Domains in the Organic–Inorganic Layered Perovskite‐Like (C6H5C2H4NH3)2FeIICl4 Crystal. Issue 32 (7th July 2017) - Nakayama, Yuki; Nishihara, Sadafumi; Inoue, Katsuya; Suzuki, Takashi; Kurmoo, Mohamedally
Abstract: Multiferroic materials coupling ferroelasticity and ferromagnetism show strong magnetoelastic effects as magnetization is induced by mechanical stress or alternately strain induced by applying a magnetic field. These effects were reported for inorganic multiferroics such as LaCo x Sr1− x O3 . (C6 H5 C2 H4 NH3 )2 Fe II Cl4 is the first example of an organic–inorganic perovskite to exhibit such effects below the canted antiferromagnetism at T C =98 K and ferroelasticity at T C =433 K. This is shown by switching the magnetic hysteresis on and off by uniaxial pressure through the strong coupling of the magnetic and elastic domains. The spin‐canting direction was controlled by mechanical stress in the heating and cooling cycles. This unique observation gives additional impetus in the search for coupled hysteretic effect in organic–inorganic multiferroics. Abstract : Molecule‐based multiferroics : An air‐stable crystal of (C6 H5 C2 H4 NH3 )2 Fe II Cl4 shows a magnetoelastic effect below the canted antiferromagnetism ( T C =98 K) and ferroelasticity ( T C =433 K). Uniaxial stress along the b  axis leads to an exchange of the a and b axes and consequently switches off the magnetic hysteresis. This on/off switch uses the strong coupling between magnetic and elastic domains.